IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS CALISTUNG SANGGAR BIMBINGAN MUHAMMADIYAH MALAYSIA - Jayluddin Fahlefy, Moch; kuswandi, Iwan; Jamilah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Literacy skills are an important thing that must be possessed by students. Good literacy skills can help students' understanding in the learning process. There are several options that teachers can use to improve students' literacy skills, one of which is by implementing differentiated learning. The purpose of this study is to improve students' literacy skills by implementing differentiated learning. The method used is a qualitative approach with a descriptive method. The results of the study indicate that the implementation of differentiated learning provides quite good progress in students' literacy skills in Sanggar Bimbingan Muhammadiyah Malaysia.